Interleukin‐28B rs12979860 C allele: Protective against advanced fibrosis in chronic hepatitis C genotype 1 infection. Issue 7 (15th July 2014) - Kitson, Matthew T; George, Jacob; Dore, Gregory J; Leung, Reynold; Button, Peter; McCaughan, Geoffrey W; Crawford, Darrell H G; Sievert, William; Weltman, Martin D; Cheng, Wendy S C; Roberts, Stuart K; CHARIOT Study Group
Abstract Background and Aim While genetic polymorphisms upstream of the interleukin‐28B (IL28B) gene are associated with necroinflammatory activity grade in chronic hepatitis C virus genotype 1 (HCV‐1) infection, any association with fibrosis is less definitive. Pretreatment liver biopsies in a cohort of treatment‐naïve patients with HCV‐1 were analyzed to evaluate associations between liver histology, and the rs12979860 and rs8099917 IL28B single nucleotide polymorphisms. Methods Two hundred sixty‐six patients with HCV‐1 infection and pretreatment liver biopsy were tested for the rs12979860 and rs8099917 single nucleotide polymorphisms. Predictors of advanced fibrosis (METAVIR F3/4) and high activity grade (A2/3) were identified using multivariable logistic regression analysis. Results Forty‐four patients (16.5%) had advanced fibrosis and 141 patients (53.0%) high activity grade. Prevalence of rs12979860 IL28B genotype was: CC 45.7%, CT 42.7%, and TT 11.6%. Prevalence of advanced fibrosis was lower in those with IL28B CC genotype compared with those without (11.0% vs 21.3%; P = 0.03), with an increasing number of T alleles associated with a higher frequency of advanced fibrosis: CC 11.0%, CT 18.0%, TT 33.3% (P = 0.01). Predictors of advanced fibrosis on multivariate analysis were platelet count (odds ratio [OR] 0.98, 95% confidence interval [CI] 0.97–0.99; P < 0.0001), high activity grade (OR 5.68, 95% CI% 1.86–17.32; P = 0.002), IL28B rs12979860 CC genotype (OR 0.36, 95% CI 0.14–0.93; P = 0.03), and aspartate aminotransferase (OR 1.02, 95% CI 1.00–1.03; P = 0.046). No association was found between rs8099917 IL28B genotype and liver histology. Conclusions IL28B rs12979860 CC genotype appears to be independently associated with a lower prevalence of advanced fibrosis stage in HCV‐1 infection. This association warrants further evaluation.